Assessing Chinese managerial competencies from different perspectives - Yu, Wenxuan (2015)
In this study we investigated assessments of managerial competency in the context of Chinese local government public officials. Based on data collected from a 2008 survey conducted in China’s Jiangsu Province and drawing on the competing values framework developed by Quinn and Rohrbaugh (1981, 1983), we examined discrepancies in the assessment of managerial competencies through the supervisors’ self-assessments of their own competencies, subordinates’ self-assessments of their own competencies, supervisors assessments of their subordinates’ competencies, and subordinates’ assessments of their supervisors’ competencies. We found that, significant differences existed between the managerial competency assessments of public officials with leadership positions and the assessments of their subordinates. This calls into question the validity and effectiveness of supervisors’ assessments and peer assessments of managerial competencies in Chinese government. We offer both general and specific policy suggestions for improving the measurement of managerial competencies in China.